1993
DOI: 10.1111/j.1748-5827.1993.tb03899.x
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neck fractures and capital epiphyseal separations in cats

Abstract: In a retrospective study, 47 fractures of the femoral neck and 17 capital epiphyseal separations were recorded in a total of 62 animals over a 12‐year period. It was found that cats sustain femoral neck fractures more often than capital epiphyseal separations. Until cats are six months old the vast majority of lesions in the proximal femur are fractures of the neck. Between the ages of six and 12 months both lesions are equally represented. After 12 months of age no capital epiphyseal separations occur and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Treatment options for CPF have historically included conservative medical management, primary repair, and FHNE. Medical management without surgical stabilization in 1 study of cats showed hypertrophic pseudoarthrosis in all cats . Contrary to expected outcome when considering the blood supply to the feline proximal femur, primary repair in cats has been successful .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Treatment options for CPF have historically included conservative medical management, primary repair, and FHNE. Medical management without surgical stabilization in 1 study of cats showed hypertrophic pseudoarthrosis in all cats . Contrary to expected outcome when considering the blood supply to the feline proximal femur, primary repair in cats has been successful .…”
Section: Discussionmentioning
confidence: 79%
“…The CPF treatment goal is to restore a pain‐free joint with a normal function for the life of the patient while preventing the development of osteoarthritis (OA) and/or avascular necrosis. Nonsurgical treatments have predictable results of developing a nonunion, malunion, pseudoarthrosis, and/or OA . Contemporary surgical treatment options include either anatomic reduction with fracture stabilization or femoral head and neck excision (FHNE).…”
mentioning
confidence: 99%
“…They occur most often in animals less than one year of age, whereas most of the cats described here were one year of age or older. Fractures of the femoral neck and capital physis occur more commonly in male than female cats (Perez‐Aparicio and Fjeld 1993), probably as a result of the predisposition to trauma of male urban dogs and cats which, it is suggested, are more aggressive and tend to wander more and are therefore more likely to encounter trauma (Kolata and others 1974). If the lesion is primarily a fracture then the bone resorption would be secondary to the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…FRACTURES of the femoral neck are not uncommon in the cat (Bennett 1975, Hill 1977, Daly 1978, Perez‐Aparicio and Fjeld 1993) and are generally thought to be the result of trauma, although the traumatic incident is seldom witnessed. This paper describes a lesion of the proximal femoral metaphysis of the cat, characterised radiographically by bone resorption which then leads to a secondary, pathological fracture.…”
mentioning
confidence: 99%
“…Nevertheless, subtle changes early in the course of SCFE may be easier to detect with CT, when conservative treatment is still possible (8). Early surgery may also produce good results (4,5,13,20). It is questionable whether CT is indicated in cats with advanced SCFE, since radiographs are often sufficient to make a diagnosis, and the only suitable treatment option is femoral head and neck ostectomy.…”
Section: Resultsmentioning
confidence: 99%